A Tumor Ampulla Vater pada Pasien Dewasa Muda - Anggi Setiorini; Aleya Yostha Kaban; Risal Wintoko (Medula, 2021)
Ampullary tumors are known as tumors that grow at the end of the common bile duct that passes through the duodenal wall of the papilla ampullaris of the pancreatic duct and the common bile duct which then coalesces and exits through the duodenal ampulla. The most common symptoms of this tumor are signs of biliary obstruction. Tumors in the gallbladder and bile ducts are generally asymptomatic early in the course of the disease and only manifest when the tumor is at an advanced stage so that the possibility of curative resection decreases. Malignancy of the ampulla of vater often manifests at an early stage so the prognosis is likely to be better. Etiological factors include smoking and previous partial gastrectomy. There is no established association between tumors of the ampulla of Vater and drinking coffee or alcohol. This case was found in a male patient, aged 33 years who came to Dr. H. Abdoel Moelok with complaints of abdominal pain on the right side accompanied by thick tea-colored urine, enlarged stomach, shortness of breath. The results of examination and support in the form of abdominal ultrasound led to the diagnosis of an ampulla of Vater tumor. The treatment given to the patient was supportive treatment in the form of a blood transfusion of three kolf to increase the hemoglobin level before being carried out in the form of a whipple operation procedure.